PtRu-based composite bifunctional catalyst as well as preparation method and application thereof
By using PtRu-based composite dual-function catalyst in the hydrogen fuel cell anode catalyst, the problems of CO poisoning and high potential corrosion are solved, and higher resistance to CO poisoning and high potential corrosion resistance are achieved, and the service life of the catalyst is extended.
Patent Information
- Application Number
- CN202411518457.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-14
AI Technical Summary
Hydrogen fuel cell anode catalyst is prone to CO poisoning and high potential corrosion, resulting in performance attenuation.
Using PtRu-based composite dual-function catalyst, the catalyst consists of platinum-ruthenium-based metal particles, non-stoichiometric transition metal oxide HxMO3 and graphitized carbon support, to improve resistance to CO poisoning and high potential corrosion through the overflow effect and active water decomposition mechanism. performance.
It significantly improves the catalyst's resistance to CO poisoning and high potential corrosion resistance, extends the service life of the catalyst and improves the overall performance of the fuel cell.
Smart Images

Figure CN119447339A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell electrocatalysis technology, and in particular to a PtRu-based composite bifunctional catalyst and its preparation method and application. Background Art
[0002] As an efficient and clean hydrogen-to-electricity conversion device, hydrogen fuel cells play an important role in my country's energy transition. Today, my country's hydrogen mainly comes from hydrogen production from fossil energy and purification of industrial by-products. The obtained hydrogen is often mixed with a small amount of CO. However, extremely low concentrations of CO in hydrogen will cause serious degradation of fuel cell performance. This is because the Pt active sites on the anode catalyst are very susceptible to CO adsorption, thereby hindering the occurrence of hydrogen oxidation reactions. Therefore, it is necessary to develop anode catalysts with high CO resistance. At the same time, under fuel cell start-stop, variable load and other operating conditions, anode gas shortage will occur, forming a high potential, causing corrosion of the carbon support. Carbon support corrosion will cause Pt particle agglomeration, reduce the number of active sites, and cause irreversible degradation of catalytic activity. Therefore, it is of great significance to develop dual-functional anode catalysts that are resistant to CO poisoning and high-potential corrosion.
[0003] In the related art, CN 101362093 A proposes a fuel cell carbon-supported platinum composite catalyst and its preparation method. The catalyst adds a co-catalytic component, hydrogen tungsten bronze or hydrogen molybdenum bronze, to a general carbon-supported platinum catalyst. The method for preparing the catalyst is to add tungstate or molybdate to a platinum compound solution at a suitable temperature and acidity, and to carry out a chemical reduction reaction in the presence of a reducing agent. However, the technology has the following defects: the main active metal component of the catalyst (except the co-catalytic component) is Pt and does not contain other metals, the activity is low, and it does not have good resistance to CO poisoning and high-potential corrosion. The single active metal makes the co-catalytic component weak in interaction with the main catalytic component and the stability is poor; at the same time, the synthesis method cannot control the morphology of hydrogen tungsten bronze or hydrogen molybdenum bronze, and requires the addition of a complexing agent that is not easy to completely remove, thereby affecting the catalytic activity. CN 101176844A proposes a platinum-based composite catalyst for a direct methanol fuel cell anode catalyst, and its basic structural formula is Pt-H xWO3, where (0 < x ≤ 1), is prepared by electro-depositing a mixed solution of H2SO4, H2PtCl6, and Na2WO4 at a certain concentration on a carbonaceous material within a certain potential range using cyclic voltammetry to obtain the anode catalyst for the direct methanol fuel cell. However, this technology has the following defects: The main active metal component of the catalyst (excluding the co-catalytic component) is Pt and does not contain other metals, resulting in low activity and lacking good anti-CO poisoning and anti-high potential corrosion functions. The single active metal makes the interaction between the co-catalytic component and the main catalytic component weak and the stability poor. At the same time, the synthesis method cannot control the morphology of hydrogen tungsten bronze or hydrogen molybdenum bronze. When synthesized by electro-deposition, the size of Pt particles is difficult to control and there are difficulties in mass production scale-up. In addition, adhesives are required for electro-depositing on carbonaceous materials such as carbon nanotubes and activated carbon, which affects the activity and is difficult to prepare. CN 103606687 A proposes a porous array Pt-p-H for the anode catalyst of a direct methanol fuel cell x MoO3 and its preparation method: A single-layer PS template is formed on ITO conductive glass by spin coating; HCHO is added to the molybdic acid solution to generate hydrogen molybdenum bronze sol; Using the sol-gel method, the hydrogen molybdenum bronze is dropped onto the ITO conductive glass carrying the PS template, and it is filled in the gaps of the PS template. After drying, the PS template is removed with toluene solution to obtain porous array H x MoO3; Using the electrochemical method of pulsed voltage, porous array H x MoO3 is electro-deposited in the H2PtCl6 solution to reduce the platinum precursor to nano platinum. This technology has the following defects: The main active metal component of the catalyst (excluding the co-catalytic component) is Pt and does not contain other metals, resulting in low activity and lacking good anti-CO poisoning and anti-high potential corrosion functions; The catalyst does not contain a carrier and has low conductivity; The synthesis process is relatively cumbersome. The spin coating method easily makes the template unevenly distributed, and when synthesized by electro-deposition, the size of Pt particles is difficult to control and there are difficulties in mass production scale-up. Summary of the Invention
[0004] To solve the problems of easy CO poisoning and high potential corrosion of the anode catalyst of hydrogen fuel cells, an object of the present application is to provide a PtRu-based composite bifunctional catalyst. This catalyst is a supported catalyst, and the support is a composite of platinum-ruthenium-based metal particles and non-stoichiometric transition metal oxide H x MO3 (M = W or / and Mo), and the carrier is a graphitized carbon carrier. Among them, the metal PtRu plays an anti-CO poisoning role, and the non-stoichiometric transition metal oxide H x MO3 (M = W or / and Mo) plays the role of a proton acceptor to promote the occurrence of the hydrogen oxidation reaction. At the same time, H xMO3 can enhance the dual-function mechanism of the carbon monoxide oxidation reaction and improve the catalyst's resistance to CO poisoning. In addition, the graphitized carbon support with a specific graphite crystallite size has excellent high-potential corrosion resistance and metal dispersion, greatly reducing the metal agglomeration and performance degradation of the catalyst caused by high-potential corrosion of the support.
[0005] Another object of the present application is to provide a method for preparing a PtRu-based composite bifunctional catalyst to solve the problems that the synthesis process of this type of catalyst is relatively complicated, the transition metal oxide is unevenly distributed, the interaction force with the active metal is weak, the size of the Pt particles is difficult to control, and there are difficulties in mass production and expansion.
[0006] Another object of the present application is to provide an electrode.
[0007] Another object of the present application is to provide a fuel cell.
[0008] To achieve the above-mentioned object, the first aspect of the present application proposes a PtRu-based composite bifunctional catalyst, comprising a carrier and a support supported on the carrier, wherein the carrier comprises a graphitized carbon carrier; the support comprises platinum-ruthenium-based metal particles and a chemical formula H x A compound of MO3, wherein M includes W and / or Mo, and 0<x≤2.
[0009] In some embodiments, the mass ratio of platinum in the platinum-ruthenium-based metal particles to the graphitized carbon support is 1:(1-6).
[0010] In some embodiments, in the platinum-ruthenium-based metal particles, the molar ratio of platinum to ruthenium is 1:(0.5-3), preferably 1:(1-2).
[0011] In some embodiments, the platinum in the platinum-ruthenium-based metal particles is x The molar ratio of the compound of MO3 is 1:(0.1-1).
[0012] In some embodiments, the chemical formula is H x MO3 compounds are non-stoichiometric transition metal oxides with electrical conductivity.
[0013] In some embodiments, when M includes W, 0<x≤1.
[0014] In other embodiments, when M includes Mo, 0<x≤2.
[0015] In some embodiments, the chemical formula is H x The compound of MO3 is at least one of hydrogen molybdenum bronze and green tungsten bronze.
[0016] In some embodiments, the average particle size of the platinum-ruthenium-based metal particles is 2-5 nm.
[0017] In some embodiments, the chemical formula is H x The compound of MO3 is amorphous or granular.
[0018] In some embodiments, the graphitized carbon support has a graphite crystallite diameter of 1-4 nm in the carbon (002) crystal plane.
[0019] In some embodiments, the specific surface area of the graphitized carbon support is 200-700 m 2 / g.
[0020] In some embodiments, the platinum-ruthenium-based metal particles further include a doping metal, and the doping metal includes at least one of Ce, La, Sm, Mo, Ti, V, Sn, Bi, W, and Au, preferably at least one of Ce, La, and Sm.
[0021] In some embodiments, the molar ratio of platinum to the doping metal in the platinum-ruthenium-based metal particles is 1:(0.1-0.5).
[0022] The second aspect of the present application provides a method for preparing a PtRu-based composite bifunctional catalyst, comprising:
[0023] calcining the carbon source to obtain graphitized carbon;
[0024] A precursor of M is first mixed with the graphitized carbon to obtain a first mixture; the M includes W and / or Mo;
[0025] The precursor of M in the first mixture is reduced to an amorphous H x MO3 or granular H x MO3, to obtain a second mixture;
[0026] performing a second mixing of a metal salt with the second mixture to obtain a third mixture; the metal salt comprises a platinum salt or a ruthenium salt, or the metal salt comprises a platinum salt, a ruthenium salt and a doped metal salt; the doped metal salt comprises at least one of a cerium salt, a lanthanum salt, a samarium salt, a molybdenum salt, a titanium salt, a vanadium salt, a tin salt, a bismuth salt, a tungsten salt, and a gold salt;
[0027] A first reducing agent is added to the third mixture to carry out a first reduction reaction, reducing the metal ions in the metal salt to metal, thereby obtaining the PtRu-based composite bifunctional catalyst.
[0028] In some embodiments, the calcining is performed under an inert atmosphere.
[0029] In some embodiments, the inert gas includes but is not limited to at least one of nitrogen, argon, and helium.
[0030] In some embodiments, the calcination temperature is 1000-2000° C., and the calcination time is 1-4 hours.
[0031] In some embodiments, the precursor of M includes at least one of ammonium tungstate, sodium tungstate, potassium tungstate, tungsten oxide, ammonium molybdate, sodium molybdate, potassium molybdate, and molybdenum oxide.
[0032] In some embodiments, the first mixing method is ball milling or mechanical stirring, and when the first mixing method is ball milling, the rotation speed of the ball mill is 50-200 rpm, and the ball milling time is 3-5 hours.
[0033] In some embodiments, the second mixing method is mechanical stirring, the rotation speed of the mechanical stirring is 150-600 rpm, and the time of the mechanical stirring is 0.5-3 hours.
[0034] In some embodiments, the first reducing agent comprises at least one of sodium borohydride solution, ascorbic acid, sodium citrate, and sodium formate.
[0035] In some embodiments, the temperature of the first reduction reaction is 5-98° C., and the time of the first reduction reaction is 0.5-3 h.
[0036] In some embodiments, the precursor of M in the first mixture is reduced to an amorphous H x MO3, comprising: adding a second reducing agent to the first mixture to perform a second reduction reaction.
[0037] In some embodiments, the second reducing agent includes at least one of substance A, ascorbic acid, sodium citrate, sodium formate, sodium borohydride, and ethylene glycol, and the substance A includes zinc powder and hydrochloric acid.
[0038] In some embodiments, the temperature of the second reduction reaction is 10-30° C., and the time of the second reduction reaction is 0.5-1 h.
[0039] In other embodiments, the precursor of M in the first mixture is reduced to granular H x MO3, comprising: sequentially vacuum drying and sintering the first mixture.
[0040] In some embodiments, the sintering temperature is 100-500° C., and the sintering time is 1-3 hours.
[0041] The third aspect of the present application proposes an electrode, comprising the PtRu-based composite bifunctional catalyst described in the present application or the PtRu-based composite bifunctional catalyst prepared by the preparation method of the PtRu-based composite bifunctional catalyst described in the present application.
[0042] A fourth aspect of the present application provides a fuel cell comprising a cathode, an anode and a separator, wherein the anode is the anode described in the present application.
[0043] In some embodiments, the fuel cell is a hydrogen fuel cell.
[0044] The PtRu-based composite bifunctional catalyst described in this application can at least bring the following beneficial effects:
[0045] 1. The catalyst is a supported catalyst, and the supported material is platinum ruthenium-based metal particles and non-stoichiometric transition metal oxide H x The composite of MO3 (M=W or / and Mo) is supported by graphitized carbon. In the hydrogen oxidation reaction, the active hydrogen adsorbed on the platinum surface can be converted to H x Overflow effect occurs on the surface of MO3 (M=W or / and Mo), H x MO3 (M=W or / and Mo) acts as a proton acceptor, thereby promoting the occurrence of hydrogen oxidation reaction. x There is active water bonding on MO3 (M=W or / and Mo). This weakly bonded water is more easily decomposed than the water in the electrolyte under the catalysis of Ru. The formation potential of Ru(OH)x is more negative, which strengthens the bifunctional mechanism of carbon monoxide oxidation reaction and weakens the anode polarization caused by CO poisoning. In addition, H x MO3 can enhance the dual-function mechanism of the carbon monoxide oxidation reaction and improve the catalyst's resistance to CO poisoning. Finally, the graphitized carbon support with a specific graphite crystallite size has excellent high-potential corrosion resistance and metal dispersion, greatly reducing the metal agglomeration and performance degradation of the catalyst caused by high-potential corrosion of the support.
[0046] 2. The PtRu-based metal particles also include doping metals, which are used to change the electronic effect of the PtRu alloy, reduce the binding energy of CO, and weaken the adsorption capacity of CO on the catalyst, thereby improving the CO poisoning resistance. On the other hand, the doping metal plays a role in enhancing the interaction with H x MO3 (M=W or / and Mo) binding force, thereby enhancing H x MO3 (M=W or / and Mo) promotes the hydrogen oxidation reaction (ie, catalytic reaction) and anti-CO activity, and improves the stability of the composite catalyst.
[0047] The preparation method of the PtRu-based composite bifunctional catalyst described in this application can at least bring the following beneficial effects:
[0048] This synthetic method is relatively simple, easy to scale up, and can control H x The morphology of MO3 (M=W or / and Mo). Amorphous H x MO3 has a porous structure with a large specific surface area, which can provide pores for the diffusion of reaction gases and a specific surface area for the support of PtRu-based metal particles. It is easy to combine with PtRu-based metal particles and has better activity. x The advantage of MO3 is that the metal oxide has stronger crystallinity, higher conductivity, and better chemical stability. The mixing method of the graphitized carbon carrier and the tungsten / molybdenum precursor is ball milling. Due to the difference in density between the graphitized carbon carrier and the tungsten / molybdenum precursor, ball milling can mix the two more evenly. During the ball milling process, due to the action of mechanical force, the micropore volume of the graphitized carbon carrier increases, and the specific surface area increases, which is more conducive to the uniform loading of PtRu-based metals, thereby improving the overall performance of the catalyst. At the same time, after the graphitized carbon carrier is ball milled, a certain degree of defects and functional groups will be generated on the surface, which increases the surface activity of the carbon carrier, is conducive to the interaction with the metal precursor, and improves the bonding between the graphitized carbon carrier and the PtRu-based metals and H x The binding force of MO3 metal oxides promotes the stability of the catalyst.
[0049] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.
[0051] in:
[0052] Figure 1 The flowchart of the preparation method of the PtRu-based composite bifunctional catalyst is shown as an exemplary embodiment of the present application.
[0053] Figure 2 This is a comparison chart of the CO poisoning resistance of the catalysts of Example 1, Example 2, Comparative Example 5, and Comparative Example 4, wherein:
[0054] a is a graph showing the CO poisoning resistance of the commercial platinum-carbon catalyst of Comparative Example 4;
[0055] b is a graph showing the CO poisoning resistance of the commercial platinum-ruthenium catalyst of Comparative Example 5;
[0056] c is a graph showing the CO poisoning resistance of the catalyst prepared in Example 1;
[0057] d is the anti-CO poisoning performance diagram of the catalyst prepared in Example 2.
[0058] Figure 3 It is a comparative diagram of the anti-CO poisoning stability curves of the catalysts of Example 1, Example 2, Comparative Example 5, and Comparative Example 4.
[0059] Figure 4 It is a comparative diagram of the high-potential carrier durability curves of the catalysts of Example 1, Example 2, Comparative Example 5, and Comparative Example 4.
[0060] Figure 5 It is an X-ray diffraction (XRD) test diagram of the (002) crystal plane of the graphitized carbon support prepared in step (1) of Example 1, Example 4, and Example 5. Detailed implementation manners
[0061] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the drawings. The embodiments described below by referring to the drawings are exemplary and are intended to explain the present application, but should not be construed as a limitation to the present application.
[0062] In the present application, the disclosure of a numerical range includes all values within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given for these ranges.
[0063] In the present application, the raw materials, equipment, etc. involved, unless otherwise specified, are raw materials and equipment that can be obtained through commercial channels or prepared by known methods; the methods involved, unless otherwise specified, are conventional methods.
[0064] <PtRu-based composite bifunctional catalyst>
[0065] The PtRu-based composite bifunctional catalyst of the embodiments of the present application includes a support and a load supported on the support. The support includes a graphitized carbon support; the load includes platinum-ruthenium-based metal particles and a compound with the chemical formula H x MO3, where M includes W or / and Mo, and 0 < x ≤ 2.
[0066] In some embodiments, part of the platinum-ruthenium-based metal particles are distributed on the graphitized support, and part are coated on the surface of at least part of the compound with the chemical formula H x MO3.
[0067] In some embodiments, the mass ratio of platinum in the platinum-ruthenium-based metal particles to the graphitized carbon carrier is 1:(1-6), including but not limited to 1:1, 1:2, 1:3, 1:4, 1:5 or 1:6. The mass ratio of platinum in the platinum-cobalt-based metal particles to the graphitized carrier is within the above range, which can make the metal particles in the catalyst evenly dispersed and increase the number of active sites. At the same time, the anode catalyst layer of the fuel cell will have a suitable thickness, which is conducive to gas mass transfer and water management; at the same time, it can better resist carbon corrosion under high potential and show better stability and reliability during long-term operation. If it is less than 1:6, the catalyst layer of the membrane electrode in the fuel cell is too thick, affecting gas mass transfer. If it is greater than 1:1, the nanoparticles will be easily agglomerated, the electrochemical area will be small, and the metal utilization rate will be low.
[0068] In some embodiments, the molar ratio of platinum to ruthenium in the platinum-ruthenium-based metal particles is 1:(0.5-3), including but not limited to 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5 or 1:3.
[0069] As a preferred example, in the platinum-ruthenium-based metal particles, the molar ratio of platinum to ruthenium is 1:(1-2).
[0070] In some embodiments, the platinum in the platinum-ruthenium-based metal particles is x The molar ratio of the compound of MO3 is 1:(0.1-1), including but not limited to 1:0.1, 1:0.25, 1:0.5, 1:0.75 or 1:1, etc.
[0071] In some embodiments, the chemical formula is H x MO3 compounds are non-stoichiometric transition metal oxides with electrical conductivity.
[0072] In some embodiments, when M includes W, 0<x≤1.
[0073] In other embodiments, when M includes Mo, 0<x≤2.
[0074] As an optional example, the chemical formula is H x The compound of MO3 is at least one of hydrogen molybdenum bronze and green tungsten bronze.
[0075] In some embodiments, the average particle size of the platinum-ruthenium-based metal particles is 2-5 nm, including but not limited to 2 nm, 3 nm, 4 nm or 5 nm.
[0076] In some embodiments, the chemical formula is H x The compound of MO3 is amorphous. xMO3 is a porous structure with a large specific surface area, which can provide pores for the diffusion of reaction gases and a specific surface area for the support of PtRu-based metal particles. It is easy to combine with PtRu-based metal particles and has better activity.
[0077] In other embodiments, the chemical formula is H x The compound of MO3 is in granular form. x The advantages of MO3 are that the metal oxide has stronger crystallinity, higher conductivity and better chemical stability.
[0078] In some embodiments, the graphitized carbon support has a graphite crystallite diameter of 1-4 nm in the carbon (002) crystal plane. Such graphitized carbon supports have improved high-potential corrosion resistance and metal dispersion, significantly reducing metal agglomeration and performance degradation of the catalyst caused by high-potential corrosion of the support.
[0079] For example, the graphite crystallite diameter of the graphitized carbon support at the carbon (002) crystal plane includes but is not limited to 1 nm, 2 nm, 3 nm or 4 nm.
[0080] In the embodiment of the present application, the graphite crystallite calculation process is:
[0081] The catalyst was subjected to X-ray diffraction (XRD) testing, and fitting was performed based on the carbon (002) crystal plane of the test pattern. The carbon crystallite diameter was calculated based on the Scherrer formula (Equation 1):
[0082] D = K × λ / (β × cosθ) Formula 1
[0083] In formula 1:
[0084] K-constant: For spherical particles, when β is the half-width height, K is taken as 0.89;
[0085] λ - X-ray wavelength, in nanometers (nm);
[0086] β - diffraction peak half-maximum width (FWHM), in radians (rad);
[0087] θ - diffraction angle, in degrees (°).
[0088] In some embodiments, the specific surface area of the graphitized carbon support is 200-700 m 2 / g, including but not limited to 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g or 700m 2 / g, etc.
[0089] In some embodiments, the platinum-ruthenium-based metal particles further include a doping metal. In the embodiments of the present application, the doping metal is used to, on the one hand, change the electronic effect of the PtRu alloy, reduce the binding energy of CO, and weaken the adsorption capacity of CO on the catalyst, thereby improving the CO poisoning resistance; on the other hand, it plays a role in enhancing the reaction with H x MO3 (M=W or / and Mo) binding force, thereby enhancing H x MO3 (M=W or / and Mo) promotes the hydrogen oxidation reaction (ie, catalytic reaction) and anti-CO activity, and improves the stability of the composite catalyst.
[0090] As an optional example, the doped metal includes at least one of Ce, La, Sm, Mo, Ti, V, Sn, Bi, W, and Au, preferably at least one of Ce, La, and Sm.
[0091] In some embodiments, the molar ratio of platinum to the doping metal in the platinum-ruthenium-based metal particles is 1:(0.1-0.5), including but not limited to 1:0.1, 1:0.2, 1:0.3, 1:0.4 or 1:0.5.
[0092] The PtRu-based composite bifunctional catalyst of the embodiment of the present application can at least bring the following beneficial effects:
[0093] 1. The catalyst is a supported catalyst, and the supported material is platinum ruthenium-based metal particles and non-stoichiometric transition metal oxide H x The composite of MO3 (M=W or / and Mo) is supported by graphitized carbon. In the hydrogen oxidation reaction, the active hydrogen adsorbed on the platinum surface can be converted to H x Overflow effect occurs on the surface of MO3 (M=W or / and Mo), H x MO3 (M=W or / and Mo) acts as a proton acceptor, thereby promoting the occurrence of hydrogen oxidation reaction. x There is active water bonding on MO3 (M=W or / and Mo). This weakly bonded water is more easily decomposed than the water in the electrolyte under the catalysis of Ru. The formation potential of Ru(OH)x is more negative, which strengthens the bifunctional mechanism of carbon monoxide oxidation reaction and weakens the anode polarization caused by CO poisoning. In addition, H x MO3 can enhance the dual-function mechanism of the carbon monoxide oxidation reaction and improve the catalyst's resistance to CO poisoning. Finally, the graphitized carbon support with a specific graphite crystallite size has excellent high-potential corrosion resistance and metal dispersion, greatly reducing the metal agglomeration and performance degradation of the catalyst caused by high-potential corrosion of the support.
[0094] 2. The PtRu-based metal particles also include doped metals. On the one hand, it is used to change the electronic effect of the PtRu alloy, reduce the binding energy of CO, weaken the adsorption ability of CO on the catalyst, and thus improve the anti-CO poisoning performance. On the other hand, the doped metals play a role in enhancing the binding force with H x MO3 (M = W or / and Mo), thereby enhancing H x the promoting effect of MO3 (M = W or / and Mo) on the hydrogen oxidation reaction (i.e., the catalytic reaction) and the anti-CO activity, and improving the stability of the composite catalyst.
[0095] <Preparation Method of PtRu-based Composite Bifunctional Catalyst>
[0096] The preparation method of the PtRu-based composite bifunctional catalyst of the embodiments of the present application can be used to prepare the PtRu-based composite bifunctional catalyst of the embodiments of the present application.
[0097] Figure 1 It is a flowchart of the preparation method of the PtRu-based composite bifunctional catalyst shown in an exemplary embodiment of the present application.
[0098] As Figure 1 shown, the preparation method of the PtRu-based composite bifunctional catalyst includes the following steps:
[0099] S101. Calcinate the carbon source to obtain graphitized carbon.
[0100] In some embodiments, the carbon source includes but is not limited to at least one of activated carbon, carbon black, etc.
[0101] As a preferred example, the carbon source is activated carbon.
[0102] In some embodiments, the calcination is carried out in an inert atmosphere.
[0103] In some embodiments, the inert gas includes but is not limited to at least one of nitrogen, argon, helium, etc.
[0104] In some embodiments, the temperature of the calcination is 1000 - 2000 °C, including but not limited to 1000 °C, 1250 °C, 1500 °C, 1750 °C or 2000 °C, etc. In the embodiments of the present application, when the calcination temperature is within the above range, graphitized carbon carriers with a specific graphite microcrystal size (for example, having a graphite microcrystal diameter of 1 nm to 4 nm on the carbon (002) crystal plane) can be obtained; when the calcination temperature is lower than 1000 °C, the graphitization effect is insufficient, the graphite microcrystal diameter is small, resulting in a poor high potential corrosion resistance effect; when the calcination temperature is higher than 2000 °C, the specific surface area of the graphitized carbon carrier is too low, the loading is more difficult, the metal dispersion is poor, and the number of active sites is affected.
[0105] In some embodiments, the calcination time is 1-4 hours, including but not limited to 1 hour, 2 hours, 3 hours or 4 hours.
[0106] S102, performing a first mixing of a precursor of M and the graphitized carbon to obtain a first mixture; the M includes W and / or Mo.
[0107] In some embodiments, the molar ratio of the precursor of M to the graphitized carbon is (0.1-1):(16.25-97.5), including but not limited to 0.1:56, 1:56, 0.55:16.25, 0.55:97.5 or 0.55:56.
[0108] In some embodiments, the precursor of M includes but is not limited to at least one of ammonium tungstate, sodium tungstate, potassium tungstate, tungsten oxide, ammonium molybdate, sodium molybdate, potassium molybdate, molybdenum oxide, and the like.
[0109] In some embodiments, the first mixing method is ball milling or mechanical stirring.
[0110] In some embodiments, when the first mixing method is ball milling, the first mixing method is ball milling.
[0111] In some embodiments, the ball milling speed is 50-200 rpm, including but not limited to 50 rpm, 100 rpm, 150 rpm or 200 rpm.
[0112] In some embodiments, the ball milling time is 3-5 hours, including but not limited to 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours.
[0113] S103, reducing the precursor of M in the first mixture to an amorphous H x MO3 or granular H x MO3, to obtain a second mixture.
[0114] In some embodiments, the precursor of M in the first mixture is reduced to an amorphous H x MO3, comprising: adding a second reducing agent to the first mixture to perform a second reduction reaction.
[0115] In some embodiments, the molar ratio of the M precursor to the second reducing agent in the first mixture is 1:(2-10), including but not limited to 1:3, 1:5, 1:7.5, or 1:9.
[0116] In some embodiments, the second reducing agent includes but is not limited to at least one of substance A, ascorbic acid, sodium citrate, sodium formate, sodium borohydride, ethylene glycol, etc., and the substance A includes zinc powder and hydrochloric acid.
[0117] For example, the substance A is zinc powder and hydrochloric acid. Preferably, the concentration of the hydrochloric acid is 0.01 mmol / L, and the molar ratio of zinc powder to hydrochloric acid is 1:(2-5), including but not limited to 1:2, 1:3, 1:4 or 1:5.
[0118] In some embodiments, the temperature of the second reduction reaction is 10-30°C, including but not limited to 10°C, 15°C, 20°C, 25°C or 30°C.
[0119] In some embodiments, the second reduction reaction time is 0.5-1 h, including but not limited to 0.5 h, 0.8 h or 1 h.
[0120] In other embodiments, the precursor of M in the first mixture is reduced to granular H x MO3, comprising: vacuum drying and sintering the first mixture in sequence.
[0121] In some embodiments, the sintering temperature is 100-500°C, including but not limited to 100°C, 200°C, 300°C, 400°C or 500°C.
[0122] In some embodiments, the sintering time is 1-3 hours, including but not limited to 1 hour, 2 hours or 3 hours.
[0123] In some embodiments, the vacuum degree of vacuum drying is -0.1 MPa to -0.05 MPa, including but not limited to -0.1 MPa, -0.09 MPa, -0.08 MPa, -0.07 MPa, -0.06 MPa or -0.05 MPa.
[0124] In some embodiments, the vacuum drying temperature is 60-100°C, including but not limited to 60°C, 70°C, 80°C, 90°C or 100°C.
[0125] In some embodiments, the vacuum drying time is 3-8 hours, including but not limited to 4 hours, 5 hours, 6 hours or 7 hours.
[0126] S104. Perform a second mixing of a metal salt with the second mixture to obtain a third mixture; the metal salt includes a platinum salt, a ruthenium salt, or the metal salt includes a platinum salt, a ruthenium salt and a doped metal salt; the doped metal salt includes at least one of a cerium salt, a lanthanum salt, a samarium salt, a molybdenum salt, a titanium salt, a vanadium salt, a tin salt, a bismuth salt, a tungsten salt, and a gold salt.
[0127] In some embodiments, the metal salt includes metal sulfates, metal nitrates, metal chlorides, and the like.
[0128] In some embodiments, the second mixing method is mechanical stirring.
[0129] In some embodiments, the rotation speed of the mechanical stirring is 150-600 rpm, including but not limited to 150 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm or 600 rpm.
[0130] In some embodiments, the mechanical stirring time is 0.5-3 h, including but not limited to 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.
[0131] S105. Adding a first reducing agent to the third mixture to perform a first reduction reaction, reducing the metal ions in the metal salt to metal, and obtaining the PtRu-based composite bifunctional catalyst.
[0132] In some embodiments, the molar ratio of the metal salt to the first reducing agent in the third mixture is 1:(2-10), including but not limited to 1:3, 1:5, 1:7 or 1:9.
[0133] In some embodiments, the first reducing agent includes but is not limited to at least one of sodium borohydride solution, ascorbic acid, sodium citrate, sodium formate, and the like.
[0134] Exemplarily, the first reducing agent is a 2-5 wt% sodium borohydride aqueous solution, such as a 3 wt% sodium borohydride aqueous solution, a 4 wt% sodium borohydride aqueous solution or a 5 wt% sodium borohydride aqueous solution.
[0135] In some embodiments, the temperature of the first reduction reaction is 5-98°C, including but not limited to 5°C, 20°C, 40°C, 60°C, 80°C or 98°C.
[0136] In some embodiments, the first reduction reaction time is 0.5-3 h, including but not limited to 0.5 h, 1 h, 1.5 h, 2 h or 2.5 h.
[0137] The preparation method of the PtRu-based composite bifunctional catalyst described in this application can at least bring the following beneficial effects:
[0138] This synthetic method is relatively simple, easy to scale up, and can control H x The morphology of MO3 (M=W or / and Mo). Amorphous H xMO3 has a porous structure with a large specific surface area, which can provide pores for the diffusion of reaction gases and a specific surface area for the support of PtRu-based metal particles. It is easy to combine with PtRu-based metal particles and has better activity. x The advantage of MO3 is that the metal oxide has stronger crystallinity, higher conductivity, and better chemical stability. The mixing method of the graphitized carbon carrier and the tungsten / molybdenum precursor is ball milling. Due to the difference in density between the graphitized carbon carrier and the tungsten / molybdenum precursor, ball milling can mix the two more evenly. During the ball milling process, due to the action of mechanical force, the micropore volume of the graphitized carbon carrier increases, and the specific surface area increases, which is more conducive to the uniform loading of PtRu-based metals, thereby improving the overall performance of the catalyst. At the same time, after the graphitized carbon carrier is ball milled, a certain degree of defects and functional groups will be generated on the surface, which increases the surface activity of the carbon carrier, is conducive to the interaction with the metal precursor, and improves the bonding between the graphitized carbon carrier and the PtRu-based metals and H x The binding force of MO3 metal oxides promotes the stability of the catalyst.
[0139] <Electrode>
[0140] The electrode of the embodiment of the present application includes the PtRu-based composite bifunctional catalyst of the embodiment of the present application or the PtRu-based composite bifunctional catalyst prepared by the preparation method of the PtRu-based composite bifunctional catalyst of the embodiment of the present application.
[0141] <Fuel Cell>
[0142] The fuel cell according to the embodiment of the present application includes a cathode, an anode and a diaphragm, wherein the anode is the anode according to the embodiment of the present application.
[0143] As a preferred example, the fuel cell is a hydrogen fuel cell.
[0144] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0145] 1. Examples and Comparative Examples
[0146] Example 1
[0147] The preparation method of the PtRu-based composite bifunctional catalyst of this embodiment comprises the following steps:
[0148] (1) Activated carbon was calcined at 1500℃ for 3h in nitrogen atmosphere to obtain graphite crystallite with a diameter (carbon (002) crystal plane) of 3.2nm and a specific surface area of 400m 2 / g of graphitized carbon.
[0149] (2) Tungsten oxide containing W (0.92 g, 0.005 mol) and 6 g of graphitized carbon were mixed by ball milling at a ball milling speed of 200 rpm for 3 h to obtain a first mixture.
[0150] (3) Add 300 g of water to the first mixture, and slowly add 150 mL of 0.1 M hydrochloric acid and 0.4 g of Zn powder to reduce the tungsten oxide in the first mixture to amorphous H x WO3 (0<x≤1), to obtain a second mixture.
[0151] (4) Chloroplatinic acid containing Pt (1.95 g, 0.01 mol), ruthenium chloride containing Ru (1.52 g, 0.015 mol), and lanthanum nitrate containing La (0.35 g, 0.0025 mol) were mixed with the second mixture, 100 g of water was added, and the mixture was mechanically stirred at a speed of 300 rpm for 2 h to obtain a third mixture.
[0152] (5) 50 g of sodium borohydride solution (5 wt% sodium borohydride aqueous solution) was added to the third mixture, and the mixture was stirred at 10° C. for 0.5 h to reduce the metal salts (i.e., chloroplatinic acid, ruthenium chloride, and lanthanum nitrate) to metal (i.e., Pt, Ru, and La) particles.
[0153] (6) The product obtained in step (5) is dried to obtain the PtRu-based composite bifunctional catalyst of this embodiment, which is labeled as PtRuLa-H x WO 3(无定形) / C.
[0154] Example 2
[0155] This embodiment is basically the same as embodiment 1, except that:
[0156] Step (3) is to vacuum dry the first mixture in a vacuum drying oven at 80°C and a vacuum degree of -0.1 MPa for 5 h, and then sinter in a tube furnace at 350°C for 2 h to reduce the tungsten oxide in the first mixture to granular H x WO3(0<x≤1).
[0157] In step (6), the PtRu-based composite bifunctional catalyst of this embodiment is marked as PtRuLa-H x WO 3(颗粒) / C.
[0158] Example 3
[0159] This embodiment is basically the same as embodiment 1, except that:
[0160] In step (2), "tungsten oxide containing W (0.92 g, 0.005 mol)" was replaced with "molybdenum oxide containing Mo (0.48 g, 0.005 mol)".
[0161] In step (3), the molybdenum oxide in the first mixture is reduced to an amorphous H x MoO3(0<x≤2).
[0162] In step (6), the PtRu-based composite bifunctional catalyst of this embodiment is marked as PtRuLa-H x MoO 3(无定形) / C.
[0163] Example 4
[0164] The preparation method of the PtRu-based composite bifunctional catalyst of this embodiment comprises the following steps:
[0165] (1) Activated carbon was calcined at 1000 °C for 4 h in an argon atmosphere to obtain graphite crystallite with a diameter (carbon (002) crystal plane) of 2.1 nm and a specific surface area of 700 m 2 / g of graphitized carbon.
[0166] (2) Ammonium tungstate containing W (0.18 g, 0.001 mol) and 1.95 g of graphitized carbon were mixed by ball milling at a ball milling speed of 50 rpm for 5 h to obtain a first mixture.
[0167] (3) Add 300g of water to the first mixture, slowly add 2g of ascorbic acid, and heat at 85℃ for 6h to reduce the ammonium tungstate in the first mixture to amorphous H x WO3 (0<x≤1), to obtain a second mixture.
[0168] (4) Chloroplatinic acid containing Pt (1.95 g, 0.01 mol), ruthenium chloride containing Ru (3.03 g, 0.03 mol), and cerium nitrate containing Ce (0.437 g, 0.001 mol) were mixed with the second mixture, 100 g of water was added, and the mixture was mechanically stirred at a speed of 150 rpm for 3 h to obtain a third mixture.
[0169] (5) 34 g of sodium borohydride solution (5 wt% sodium borohydride aqueous solution) was added to the third mixture, and the mixture was stirred at 15° C. for 1 h to reduce the metal salts (i.e., chloroplatinic acid, ruthenium chloride, and cerium nitrate) to metal (i.e., Pt, Ru, and Ce) particles.
[0170] (6) The product obtained in step (5) is dried to obtain the PtRu-based composite bifunctional catalyst of this embodiment, which is labeled as PtRuCe-H x WO 3(无定形) / C.
[0171] Example 5
[0172] The preparation method of the PtRu-based composite bifunctional catalyst of this embodiment comprises the following steps:
[0173] (1) Activated carbon was calcined at 2000℃ for 1h in an argon atmosphere to obtain graphite crystallite with a diameter (carbon (002) crystal plane) of 4.0nm and a specific surface area of 200m 2 / g of graphitized carbon.
[0174] (2) Sodium molybdate containing Mo (0.96 g, 0.01 mol) and 11.7 g of graphitized carbon were mixed by ball milling at a ball milling speed of 200 rpm for 3 h to obtain a first mixture.
[0175] (3) The first mixture was vacuum dried in a vacuum drying oven at 100°C and a vacuum degree of -0.1 MPa for 5 h, and then sintered in a tube furnace at 500°C for 1 h to reduce the sodium molybdate in the first mixture to granular H x MoO3 (0<x≤2), to obtain a second mixture.
[0176] (4) Chloroplatinic acid containing Pt (1.95 g, 0.01 mol), ruthenium chloride containing Ru (0.51 g, 0.005 mol), and samarium nitrate containing Sm (0.75 g, 0.005 mol) were mixed with the second mixture, 100 g of water was added, and the mixture was mechanically stirred at a speed of 150 rpm for 3 h to obtain a third mixture.
[0177] (5) 60 g of sodium borohydride solution (2 wt% sodium borohydride aqueous solution) was added to the third mixture and stirred at 25° C. for 0.5 h to reduce the metal salts (i.e., chloroplatinic acid, ruthenium chloride, and samarium nitrate) to metal (i.e., Pt, Ru, and Sm) particles.
[0178] (6) The product obtained in step (5) is dried to obtain the PtRu-based composite bifunctional catalyst of this embodiment, which is labeled as PtRuSm-H x MoO 3(颗粒) / C.
[0179] Figure 5 This is an X-ray diffraction (XRD) test diagram of the crystal plane of the graphitized carbon support (002) prepared in step (1) of Example 1, Example 4 and Example 5. Figure 5 Based on the Scherrer formula, the diameter of graphite crystallites in the corresponding catalyst can be obtained.
[0180] Example 6
[0181] This embodiment is basically the same as embodiment 1, except that:
[0182] In step (4), “lanthanum nitrate containing La (0.35 g, 0.0025 mol)” was removed, i.e., the catalyst did not contain metallic La;
[0183] In step (5), the metal salt (i.e., chloroplatinic acid, ruthenium chloride) is reduced to metal (i.e., Pt, Ru) particles;
[0184] In step (6), the PtRu-based composite bifunctional catalyst of this embodiment is labeled as PtRuLa-H x WO 3(无定形) / C.
[0185] (6) The product obtained in step (5) is dried to obtain the PtRu-based composite bifunctional catalyst of this embodiment, which is labeled as PtRu-H x WO3(amorphous) / C.
[0186] Example 7
[0187] This embodiment is basically the same as embodiment 2, except that:
[0188] In step (4), “lanthanum nitrate containing La (0.35 g, 0.0025 mol)” was removed, i.e., the catalyst did not contain metallic La;
[0189] In step (5), the metal salt (i.e., chloroplatinic acid, ruthenium chloride) is reduced to metal (i.e., Pt, Ru) particles;
[0190] In step (6), the PtRu-based composite bifunctional catalyst of this embodiment is marked as PtRu-H x WO 3(颗粒) / C.
[0191] Example 8
[0192] This embodiment is basically the same as embodiment 1, except that:
[0193] In step (2), the ball milling is replaced by mechanical stirring of the aqueous solution. Specifically, step (2) is:
[0194] Tungsten oxide containing W (0.92 g, 0.005 mol) was mixed with 6 g of graphitized carbon, 300 g of water was added, and the mixture was mechanically stirred at a rotation speed of 250 rpm for 3 hours to obtain a first mixture.
[0195] The catalyst in this example is labeled as PtRuLa-H x WO3(amorphous) / C 非球磨 .
[0196] Comparative Example 1
[0197] This comparative example is basically the same as Example 1, except that:
[0198] It does not contain steps (2) and (3), that is, the catalyst does not contain H x WO3.
[0199] The catalyst in this comparative example is marked as PtRuLa / C.
[0200] Comparative Example 2
[0201] This comparative example is basically the same as Example 5, except that:
[0202] It does not contain steps (2) and (3), that is, the catalyst does not contain H x MoO3.
[0203] The catalyst in this comparative example is marked as PtRuSm / C.
[0204] Comparative Example 3
[0205] This comparative example is basically the same as Example 5, except that:
[0206] The method does not include step (1), i.e., the activated carbon support is not subjected to graphitization treatment;
[0207] In step (2), “graphitized carbon” is replaced by “activated carbon”.
[0208] The catalyst of this comparative example is marked as PtRuSm-H x MoO3(granules) / C 非石墨化碳 .
[0209] Comparative Example 4
[0210] The catalyst of this comparative example is a commercial platinum-carbon catalyst, labeled Pt / C, wherein the carrier is high-surface carbon (non-graphitized carbon) and the platinum loading is 46.5 wt%.
[0211] Comparative Example 5
[0212] The catalyst in this comparative example is a commercial platinum-ruthenium catalyst, labeled PtRu / C, wherein the carrier is high-surface carbon (non-graphitized carbon), the platinum loading is 35 wt%, and the ruthenium loading is 25 wt%.
[0213] 2. Performance Testing
[0214] Using a rotating disk electrode, the catalysts synthesized in Examples 1-8 and Comparative Examples 1-5 were subjected to CO poisoning resistance, stability tests, and high-potential durability tests.
[0215] The CO poisoning resistance test method is to perform LSV test of hydrogen oxidation reaction under pure H2 and 1000ppm CO / H2, and record the limiting current decay ratio.
[0216] The anti-CO poisoning stability test method is: perform a constant potential test under 1000ppm CO / H2 and record the current decay ratio after 3000s.
[0217] The high-potential durability test method is to perform CV cycles at 1.0-1.5 V (vs RHE) and record the ECSA decay rate after 10 cycles. The electrolyte is 0.1 M HClO4 solution.
[0218] The above performance test results are detailed in Table 1 and Figure 2-4 .
[0219] Table 1 Performance test results
[0220]
[0221]
[0222] According to Table 1 and Figure 2-4 It can be seen that:
[0223] The CO poisoning resistance, CO poisoning resistance stability and high potential durability of Examples 1-8 are all better than those of commercial platinum-carbon and platinum-ruthenium catalysts.
[0224] Among them, the PtRuLa-H of Example 1 x WO 3(无定形) / C has the best anti-CO poisoning performance, mainly due to the hydrogen tungsten bronze H x WO3Q has active water bonding, which is catalyzed by Ru. x WO3 is more easily decomposed by water than water in the electrolyte, resulting in Ru(OH) x The formation potential of the PtRuLa-H in Example 1 is more negative (easier to form), which enhances the bifunctional mechanism of the carbon monoxide oxidation reaction and weakens the anode polarization caused by CO poisoning. Therefore, it is more resistant to CO poisoning than the PtRuLa / C in Comparative Example 1. x WO 3(无定形) The presence of La in the PtRu / C catalyst changes the electronic effect of the PtRu alloy, reduces the binding energy of CO, and weakens the adsorption capacity of CO on the catalyst, thereby improving the CO poisoning resistance. x WO 3(无定形) / C is more resistant to CO poisoning. At the same time, the PtRuLa-H x WO 3(无定形) / C catalyst due to the amorphous Hx WO3 is a porous structure with a large specific surface area, which has a stronger interaction force with PtRuLa particles and a larger bonding surface. After the active water is decomposed into active OH, it is easier to combine with Ru, thereby improving the CO resistance. x Compared with granular H x WO3 (Example 2) has better CO resistance.
[0225] The PtRuLa-H in Example 2 x WO 3(颗粒) / C has the best anti-CO stability, on the one hand, due to the granular H x WO3 has stronger crystallinity and more stable structure, so it is more resistant to corrosion than amorphous H x WO3 (Example 1) has a more stable promoting effect on CO resistance, and on the other hand, it is due to the x WO 3(颗粒) Metal La and H in C x WO3 is easier to form chemical bonds, has stronger binding force, and can inhibit the agglomeration of metal particles. Therefore, compared with PtRu-H in Example 7, x WO 3(颗粒) / C has better stability against CO poisoning.
[0226] PtRuSm-H x MoO 3(颗粒) / C has the best high potential durability, on the one hand, due to the x MoO 3(颗粒) The carrier of the PtRuSm-H catalyst has been graphitized, and the graphite crystals are larger and the degree of graphitization is higher. Therefore, its high potential corrosion resistance is better than that of the PtRuSm-H catalyst in comparative example 5. x MoO 3(颗粒) / C 非石墨化碳 On the other hand, the catalyst is strong. x MoO 3(颗粒) Compared with carbon supports, the catalyst has stronger tolerance to high potentials, so the high-potential corrosion resistance of the PtRuSm / C catalyst is better than that in Comparative Example 2.
[0227] In the embodiment, the mixing method of the carbon support and the tungsten / molybdenum precursor is ball milling. Due to the difference in density between the carbon support and the tungsten / molybdenum precursor, ball milling can mix the two more evenly. During the ball milling process, due to the action of mechanical force, the micropore volume of the carbon support increases, and the specific surface area increases, which is more conducive to the uniform loading of the PtRu-based metal, thereby improving the overall performance of the catalyst. At the same time, after the carbon support is ball milled, a certain degree of defects and functional groups will be produced on the surface, which improves the surface activity of the carbon support, which is conducive to enhancing the interaction between the carbon support and Mo / W and PtRu metal precursors, and enhancing the binding force between the carbon support and the metal, thereby promoting the stability of the catalyst. Example 8 is based on Example 1, and the carbon support and the tungsten precursor are changed from ball milling mixing to mechanical stirring of an aqueous solution. Example 1 PtRuLa-H x WO 3(无定形) Compared with the PtRuLa-H / C ball-milled catalyst in Example 8 x WO 3(无定形) / C 非球磨 The catalyst's CO poisoning resistance, CO poisoning stability, and high-potential durability are all improved.
[0228] In this application, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples without contradiction.
[0229] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of the technical features being referred to. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of such features. Throughout the description of this application, "plurality" means at least two, for example, two, three, etc., unless otherwise specifically defined.
[0230] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A PtRu-based composite bifunctional catalyst, characterized in that: The invention comprises a carrier and a support material supported on the carrier, wherein the carrier comprises a graphitized carbon carrier; the support material comprises platinum-ruthenium-based metal particles and a chemical formula of H x A compound of MO3, wherein M includes W and / or Mo, 0<x≤2.
2. The PtRu-based composite bifunctional catalyst according to claim 1, characterized in that: The mass ratio of platinum in the platinum-ruthenium-based metal particles to the graphitized carbon carrier is 1:(1-6); and / or, In the platinum-ruthenium-based metal particles, the molar ratio of platinum to ruthenium is 1:(0.5-3); and / or, The platinum in the platinum-ruthenium-based metal particles and the chemical formula H x The molar ratio of the compound of MO3 is 1:(0.1-1).
3. The PtRu-based composite bifunctional catalyst according to claim 1, characterized in that: The chemical formula is H x The compound of MO3 is a non-stoichiometric transition metal oxide having electrical conductivity; and / or, When M includes W, 0<x≤1; and / or, When M includes Mo, 0<x≤2; and / or, The chemical formula is H x The compound of MO3 is at least one of hydrogen molybdenum bronze and blue tungsten bronze.
4. The PtRu-based composite bifunctional catalyst according to claim 1, characterized in that: The average particle size of the platinum-ruthenium-based metal particles is 2-5 nm; and / or, The chemical formula is H x The compound of MO3 is amorphous or granular; and / or, The graphitized carbon carrier has a graphite crystallite diameter of 1-4 nm on the carbon (002) crystal plane; and / or, The specific surface area of the graphitized carbon carrier is 200-700m 2 / g.
5. The PtRu-based composite bifunctional catalyst according to any one of claims 1 to 4, characterized in that: The platinum-ruthenium-based metal particles also include a doping metal, and the doping metal includes at least one of Ce, La, Sm, Mo, Ti, V, Sn, Bi, W, and Au; Preferably, the doping metal is Ce, La, or Sm; Preferably, the molar ratio of platinum to the doping metal in the platinum-ruthenium-based metal particles is 1:(0.1-0.5).
6. A method for preparing a PtRu-based composite bifunctional catalyst, characterized in that: include: calcining the carbon source to obtain graphitized carbon; The precursor of M is first mixed with the graphitized carbon to obtain a first mixture; the M includes W and / or Mo; The precursor of M in the first mixture is reduced to an amorphous state H x MO3 or granular H x MO3, to obtain a second mixture; The metal salt is mixed with the second mixture for a second time to obtain a third mixture; the metal salt comprises a platinum salt and a ruthenium salt, or the metal salt comprises a platinum salt, a ruthenium salt and a doped metal salt; the doped metal salt comprises at least one of a cerium salt, a lanthanum salt, a samarium salt, a molybdenum salt, a titanium salt, a vanadium salt, a tin salt, a bismuth salt, a tungsten salt and a gold salt; A first reducing agent is added to the third mixture to carry out a first reduction reaction, so as to reduce the metal ions in the metal salt to metals, thereby obtaining the PtRu-based composite bifunctional catalyst.
7. The preparation method according to claim 6, characterized in that: The calcination is carried out under an inert atmosphere; and / or, The calcination temperature is 1000-2000°C, and the calcination time is 1-4h; and / or, The precursor of M includes at least one of ammonium tungstate, sodium tungstate, potassium tungstate, tungsten oxide, ammonium molybdate, sodium molybdate, potassium molybdate, and molybdenum oxide; and / or, The first mixing method is ball milling or mechanical stirring, and when the first mixing method is ball milling, the rotation speed of the ball mill is 50-200 rpm, and the time of the ball milling is 3-5 hours; and / or, The second mixing method is mechanical stirring, the rotation speed of the mechanical stirring is 150-600 rpm, and the time of the mechanical stirring is 0.5-3h.
8. The preparation method according to claim 6, characterized in that: The first reducing agent comprises at least one of sodium borohydride solution, ascorbic acid, sodium citrate, and sodium formate; and / or, The temperature of the first reduction reaction is 5-98° C., and the time of the first reduction reaction is 0.5-3 h; and / or, The precursor of M in the first mixture is reduced to an amorphous state H x MO3, including: adding a second reducing agent to the first mixture to perform a second reduction reaction; and / or, The precursor of M in the first mixture is reduced to particulate H x MO3, including: sequentially vacuum drying and sintering the first mixture; Preferably, the second reducing agent comprises at least one of substance A, ascorbic acid, sodium citrate, sodium formate, sodium borohydride, and ethylene glycol, and the substance A comprises zinc powder and hydrochloric acid; Preferably, the temperature of the second reduction reaction is 10-30°C, and the time of the second reduction reaction is 0.5-1h; Preferably, the sintering temperature is 100-500° C., and the sintering time is 1-3 hours.
9. An electrode, characterized in that: It comprises the PtRu-based composite bifunctional catalyst as described in any one of claims 1 to 5 or the PtRu-based composite bifunctional catalyst prepared by the preparation method as described in any one of claims 6 to 8.
10. A fuel cell comprising a cathode, an anode and a diaphragm, characterized in that: The anode is the anode as claimed in claim 9; Preferably, the fuel cell is a hydrogen fuel cell.
Citation Information
Patent Citations
Direct methanol fuel cell anode catalyzer as well as preparation method and application thereof
CN101176844A
Carbon supported platinum composite catalyst of fuel cell and preparation method thereof
CN101362093A
Anode catalyst porous array Pt-p-HxMoO3 for direct methanol fuel cell and preparation method of anode catalyst porous array Pt-p-HxMoO3
CN103606687A
Cited By
High-entropy intermetallic compound bifunctional catalyst as well as preparation method and application thereof
CN120280508A
High-entropy intermetallic compound bifunctional catalyst and preparation method and application thereof
CN120280508B